Method for preparing Prussian blue analogue material by using microcapsule slow-release technology and application of Prussian blue analogue material

The B solution is coated with microcapsule sustained release technology to control the precipitation rate of Prussian blue analogue, solving the problem of difficult to guarantee crystal quality in traditional synthesis methods, and achieving the preparation of high-quality Prussian blue analogues and excellent electrochemical properties.

CN119612550APending Publication Date: 2025-03-14DONGGUAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411842795.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Traditional methods of synthesis of Prussian blue analogs are difficult to control the rate of crystal precipitation, resulting in difficult to ensure crystal quality, and easily defects and crystallization water are generated in the structure, affecting electrochemical properties.

Method used

Microcapsule sustained release technology is used to coat the B solution by combining alginate with calcium ions to form transparent microcapsules, and the B solution is slowly released in solution A to control the precipitation rate of Prussian blue analog.

Benefits of technology

It effectively reduces the precipitation rate of Prussian blue analog, improves crystal quality, reduces defects and crystal water, and significantly improves rate performance, cycle performance and Coulomb efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612550A_ABST
    Figure CN119612550A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a Prussian blue analogue material by using a microcapsule slow release technology and application, and relates to the technical field of sodium ion battery positive electrode materials. According to the preparation method, the solution B is coated in a mode that alginate radicals are combined with calcium ions to form microcapsules containing the solution B, the microcapsules containing the solution B are added into the solution A, so that the microcapsules coating the solution B are uniformly dispersed in the solution A, the solution B is slowly released, prussian blue analogue crystals are slowly formed in a reaction system, the precipitation rate of the prussian blue analogue is reduced, and the yield of the prussian blue analogue is increased. The problem of non-uniform reaction can be effectively solved, the crystal quality is improved, and defects and crystal water are reduced. According to the method, carbonate ions are introduced to convert the calcium alginate film into insoluble calcium carbonate precipitates, weak acid is added or carbon dioxide gas is introduced to convert the water-insoluble calcium carbonate precipitates into soluble salts, and the soluble salts are removed by washing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion battery positive electrode materials, and in particular to a method for preparing a Prussian blue analog material by utilizing microcapsule sustained-release technology and application thereof. Background Art

[0002] Prussian blue analogs have become potential cathode materials for sodium-ion batteries due to their low cost and high theoretical energy density. Prussian blue analogs have a unique three-dimensional open framework structure without oxygen lattices that can achieve rapid and reversible sodium ion insertion and extraction, thus having high specific capacity, long cycle life and excellent rate performance. At the same time, their raw material resources are abundant, low in price, and the synthesis process is easy to scale up, which has great practical application potential.

[0003] The traditional method for synthesizing Prussian blue analogs is difficult to control the rate of crystal precipitation of Prussian blue analogs, which makes it difficult to ensure the quality of the crystals and easily produces many defects and water of crystallization in the structure: the traditional method for synthesizing Prussian blue analogs adopts the method of pumping B solution into A solution to solve the problem of uneven reaction. The crystal precipitation rate of Prussian blue analogs is relatively fast, and the quality of the crystals is difficult to ensure, so that many defects and water of crystallization are produced in the structure. If the nucleation rate of the crystal is much higher than the growth rate of the crystal (the growth rate of the crystal refers to the speed at which the crystal nucleus grows into a macroscopic crystal), it will cause many small crystal nuclei to compete for growth, thereby affecting the uniformity and integrity of the crystal, resulting in poor electrochemical effects such as rate effect and cycle performance of the sodium ion battery assembled with the Prussian blue analogs prepared therefrom.

[0004] Therefore, a synthetic method that can reduce the precipitation rate of Prussian blue analogs is needed. Summary of the invention

[0005] Based on the above reasons, in view of the problems or defects in the prior art, the purpose of the present invention is to provide a method and application of preparing Prussian blue analog materials using microcapsule sustained-release technology, so as to solve or at least partially solve the above technical defects in the prior art.

[0006] In order to achieve the above first object of the present invention, the technical solution adopted by the present invention is as follows:

[0007] A method for preparing a Prussian blue analog material using microcapsule sustained-release technology, the method specifically comprising the following steps:

[0008] (1) dissolving a transition metal source and a sodium source in deionized water in order according to a ratio to obtain a solution A;

[0009] Dissolve sodium ferroxine and alginate in deionized water in order according to the ratio to obtain solution B;

[0010] (2) preparing a saturated calcium source solution, heating it to 60-90° C., and then dripping the solution B described in step (1) dropwise into the saturated calcium source solution; filtering after the dripping is completed to obtain transparent microcapsules coated with the solution B;

[0011] (3) adding the transparent microcapsules containing solution B described in step (2) to solution A described in step (1) under stirring, and continuing the stirring reaction for 6-12 hours to obtain a mixed solution 1;

[0012] (4) adding carbonate to the mixed solution 1 of step (3) and stirring until completely dissolved; then continuing to add acid solution to the reaction system under stirring until the pH value of the obtained mixed solution 2 is less than 7, and filtering with suction to obtain a Prussian blue analog precursor;

[0013] (5) Drying and crushing the Prussian blue analog precursor described in step (4) to obtain a Prussian blue analog powder.

[0014] Furthermore, in the above technical solution, the transition metal source in step (1) is specifically a transition metal ion salt, wherein: the transition metal ion salt is composed of a transition metal cation and an anion, and the transition metal M is at least one of Mn, Fe, Ni, Cu, etc.; and the anion is at least one of sulfate ion, chloride ion, nitrate ion, etc.

[0015] Furthermore, in the above technical solution, the sodium source in step (1) is specifically a soluble sodium salt, for example, it can be at least one of sodium chloride, sodium citrate, sodium sulfate, sodium gluconate, etc.

[0016] Furthermore, in the above technical solution, in step (1), when preparing solution A, the mass ratio of the transition metal source, the sodium source and the deionized water is 1-5:1-4:2-5.

[0017] Furthermore, in the above technical solution, in step (1) when preparing solution A, the deionized water is preferably heated deionized water, such as deionized water at 80-90° C. The use of heated deionized water is conducive to the rapid dissolution of the transition metal source and the sodium source.

[0018] Furthermore, in the above technical solution, the alginate in step (1) includes at least one of soluble alginate containing alginate radicals such as sodium alginate, potassium alginate, and magnesium alginate.

[0019] Furthermore, in the above technical solution, in step (1), when preparing solution B, the mass ratio of sodium ferroxine, alginate and deionized water is 3-6:4-8:10.

[0020] Furthermore, in the above technical solution, in step (1) when preparing solution B, the deionized water is preferably heated deionized water, such as deionized water at 80-90° C. The use of heated deionized water is conducive to the rapid dissolution of sodium ferroxine and alginate.

[0021] Furthermore, in the above technical solution, the calcium source in the saturated calcium source solution in step (2) is specifically a soluble calcium salt, and the soluble calcium salt can be at least one of calcium chloride, tricalcium citrate, calcium gluconate, etc.

[0022] Furthermore, in the above technical solution, the volume ratio of the saturated calcium source solution to the B solution in step (2) is 5-30:1.

[0023] Furthermore, in the above technical solution, the stirring speed in step (3) is 50-150 r / min, and the speed cannot be too fast to avoid damaging the microcapsules coated with solution B.

[0024] Furthermore, in the above technical solution, during the stirring reaction in step (3), the stirring speed adopted is 100-150 r / min.

[0025] Furthermore, in the above technical solution, the carbonate in step (4) is specifically a soluble carbonate; wherein: the soluble carbonate can be at least one of sodium carbonate, potassium carbonate, ammonium carbonate, etc.

[0026] Furthermore, in the above technical solution, the acid in step (4) is at least one of citric acid, acetic acid, hydrochloric acid, etc. The pH of the mixed solution 2 is less than 7, which proves that the calcium carbonate is completely removed. And the pH value of the mixed solution 2 can only be slightly less than 7. If the mixed solution 2 is too acidic, it may cause the Prussian blue analog to decompose.

[0027] Further, in the above technical solution, in some embodiments of the present invention, the drying temperature in step (5) is 120° C. and the drying time is 24-48 hours. After crushing, a Prussian blue analog powder with lower defects, less water content and better thermal stability is obtained. After the crystal quality is improved, the capacity will be higher, the polarization will be less, and the rate performance, cycle performance including coulomb efficiency will be significantly improved.

[0028] The second object of the present invention is to provide a Prussian blue analog material prepared by the above method.

[0029] The third object of the present invention is to provide the use of the Prussian blue analogue material prepared by the above method as a positive electrode active material in a sodium ion battery.

[0030] The fourth object of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein: the active material used in the positive electrode is the Prussian blue analogue material prepared by the above-mentioned method.

[0031] The principle or mechanism involved in the present invention is as follows:

[0032] The B solution containing alginate and the saturated solution of calcium source of the present invention will form calcium alginate microcapsules instantly when the B solution is dripped into the calcium solution, and the B solution will be coated to form transparent microcapsules containing the B solution: when the alginate contacts the calcium salt, the calcium ions will undergo ion exchange reaction with the cations in the alginate. In this process, the calcium ions will form cross-linked bonds with the carboxylic acid groups in the alginate molecules, and these cross-linked bonds will connect the calcium alginate molecules together to form a three-dimensional network structure. The formation of this structure allows the originally flowing alginate to be transformed into a gel state with a certain mechanical strength, that is, a microcapsule is formed. This microcapsule does not completely prevent the seepage of the A solution, and the B solution will slowly seep out and react with the A solution.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The present invention uses alginate and calcium ions to coat the B solution to form microcapsules containing the B solution, and adds the microcapsules coated with the B solution to the A solution so that the microcapsules are evenly dispersed in the A solution and slowly release the B solution, so that the Prussian blue analog crystals are slowly formed in the reaction system, and the precipitation rate of the Prussian blue analog is reduced, which can effectively solve the problem of uneven reaction, improve the quality of crystals, and reduce defects and crystal water. Finally, the method of the present invention introduces carbonate ions to convert the calcium alginate film into an insoluble calcium carbonate precipitate, and then adds a weak acid or passes carbon dioxide gas to convert the water-insoluble calcium carbonate precipitate into a soluble salt, which is then washed and removed.

[0035] (2) The present invention can reduce the rate of crystallization of Prussian blue analogs and reduce surface defects and crystal water content of Prussian blue analogs. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 This is a process flow chart of preparing a Prussian blue analog material using microcapsule sustained-release technology in Example 1 of the present invention;

[0038] Figure 2 Schematic diagram of the structure of the three-dimensional network microcapsule formed in Example 1 of the present invention;

[0039] Figure 3 A charge and discharge cycle test diagram of a half-cell composed of the Prussian blue analogue material prepared in Example 1 of the present invention as the positive electrode active material and the sodium sheet as the negative electrode;

[0040] Figure 4 This is the XRD test pattern of the Prussian blue analog material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0041] The present invention is further described in detail below through implementation cases. This implementation case is implemented based on the technology of the present invention, and a detailed implementation method and specific operation process are now given to illustrate that the present invention is creative, but the protection scope of the present invention is not limited to the following implementation cases.

[0042] According to the information contained in this application, various changes can be easily made to the precise description of the present invention for those skilled in the art.It should be understood that the scope of the present invention is not limited to defined processes, properties or components, because these embodiments and other descriptions are only for illustrating specific aspects of the present invention.

[0043] In order to better understand the present invention but not to limit the scope of the present invention, all the numbers used in this application to express the amount, percentage, and other numerical values ​​should be understood as modified by the word "about" in all cases. Therefore, unless otherwise specified, the numerical parameters listed in the specification are approximate values, which may be changed according to the different ideal properties attempted to be obtained. Each numerical parameter should at least be regarded as obtained based on the reported significant figures and by conventional rounding methods.

[0044] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.

[0045] Example 1

[0046] A method for preparing a Prussian blue analog material using microcapsule sustained-release technology in this embodiment specifically comprises the following steps:

[0047] 1. Preparation of microcapsules

[0048] (1) Prepare solutions A and B:

[0049] Take 34g of manganese sulfate and 125g of sodium citrate, dissolve them in 100mL of hot water at 90°C to obtain solution A; take 100g of sodium ferroxine and 50g of sodium alginate, dissolve them in 100mL of hot water at 90°C to obtain solution B.

[0050] (2) Coating solution A:

[0051] Take 150g of calcium chloride powder and dissolve it in 100mL of hot water at 90°C to obtain a saturated calcium chloride solution; then transfer solution B to a syringe, add solution B dropwise to the saturated calcium chloride solution, and after the addition is completed, filter to obtain transparent microcapsules coated with solution B.

[0052] 2. Preparation of Prussian Blue Analogue Materials

[0053] (1) Solution A was transferred to a reaction kettle, the stirring speed was started at 100 r / min, and then the transparent microcapsules coated with solution B were added, and the stirring reaction was continued at 100 r / min for 6 hours to obtain a mixed solution 1;

[0054] (2) The mixed solution 1 is transferred to a beaker, 50 g of sodium carbonate powder is added, and after stirring until completely dissolved, citric acid powder is added to make the pH of the obtained mixed solution 2 less than 7, and filtered to obtain a Prussian blue analog precursor.

[0055] (3) The Prussian blue analog precursor is placed in a vacuum oven at 120° C. and vacuum dried for 24 h, and then crushed to obtain a Prussian blue analog powder.

[0056] Example 2

[0057] The method for preparing a Prussian blue analog material using microcapsule sustained-release technology in this embodiment is basically the same as that in Example 1, except that: in this embodiment, 34 g of manganese sulfate in solution A is replaced with 35 g of ferrous sulfate; the rest remains unchanged.

[0058] Example 3

[0059] The method for preparing a Prussian blue analog material using microcapsule sustained-release technology in this embodiment is basically the same as that in Example 1, except that the stirring speed of the reactor is replaced with 150 r / min from 100 r / min in this embodiment; the rest remains unchanged.

[0060] Example 4

[0061] The method for preparing a Prussian blue analog material using microcapsule sustained-release technology in this embodiment is basically the same as that in Example 1, except that 50 g of sodium alginate in solution B is replaced with 75 g of potassium alginate, and the rest remains unchanged.

[0062] Example 5

[0063] The method of preparing a Prussian blue analog material using microcapsule sustained-release technology in this embodiment is basically the same as that in Example 1, except that in this embodiment, 125 g of sodium citrate in solution A is replaced with a mixture of 100 g of sodium citrate and 50 g of sodium chloride, and the rest remains unchanged.

[0064] Comparative Example 1

[0065] The preparation method of a Prussian blue analog material in this comparative example comprises the following steps:

[0066] (1) Take 34 g of manganese sulfate and dissolve it in 100 mL of hot water at 90° C. to obtain solution A; take 100 g of sodium ferrocyanide and 125 g of sodium citrate and dissolve them in 100 mL of hot water at 90° C. to obtain solution B;

[0067] (2) transferring the solution B to a reactor, starting the stirring speed at 100 r / min, then pumping in the solution A, stirring for 6 h, and then filtering to obtain a Prussian blue analog precursor;

[0068] (3) The Prussian blue analog precursor is placed in a vacuum oven at 120° C. and vacuum dried for 24 hours, and then crushed to obtain a Prussian blue analog powder.

[0069] Structural testing:

[0070] Figure 4 This is the XRD test diagram of the Prussian blue analogue material prepared in Example 1 of the present invention. It can be seen that the Prussian blue analogue is successfully synthesized.

[0071] Electrochemical performance test:

[0072] The Prussian blue analogue materials prepared in the above Examples 1-5 and Comparative Example 1 were respectively used as positive electrode active materials to assemble button batteries, and the specific methods are as follows:

[0073] The positive electrode sheet is composed of a Prussian blue analog material, Super P conductive carbon, and PVDF polyvinylidene fluoride binder, wherein the mass ratio of the Prussian blue analog material, Super P, and PVDF is 7:1.5:1.5. The Prussian blue analog material, Super P conductive carbon, and PVDF are mixed uniformly in proportion by grinding for 20 minutes, and the uniformly mixed material is mixed with N-methylpyrrolidone (NMP) solvent, and placed on a micro ball mill and stirred for 3 hours to obtain a uniform slurry, and the slurry is evenly coated on an aluminum foil (the coating amount is 110.23 g / cm 2 ), vacuum dried in an oven at 120°C for 5 hours, and punched out a positive electrode sheet with a diameter of 12 mm using a gun press, which was weighed and set aside for use.

[0074] A sodium ion battery half-cell is formed by using a sodium sheet as the negative electrode, the positive electrode is the positive electrode sheet prepared above, the separator is a PP separator or a glass cellulose separator, and the electrolyte is a 1 mol / L sodium hexafluorophosphate solution. The test item density is 70 mA / g, the test voltage range is 2.1 V-3.9 V, and the button battery is subjected to a charge and discharge cycle test.

[0075] Figure 3 The charge and discharge cycle test diagram of a half-cell using the Prussian blue analogue material prepared in Example 1 of the present invention as the positive electrode active material and the sodium sheet as the negative electrode; it can be seen that the sodium ion battery has a first cycle discharge capacity of 165 mAh / g, and a 2000th cycle discharge capacity of 146 mAh / g.

[0076] Table 1 is a summary of the first cycle capacity, capacity after 2000 cycles, and capacity retention rate of half-cells assembled using the Prussian blue analogue materials prepared in Examples 1-5 and Comparative Example 1 as positive electrode active materials. It can be seen from the summary table that Example 4 is the most advantageous preparation condition for the material.

[0077] Table 1 Comparison of the first cycle capacity, capacity after 2000 cycles, and capacity retention rate of half-cells assembled using the Prussian blue analogue materials prepared in Examples 1-5 and Comparative Example 1 as positive electrode active materials

[0078]

Claims

1. A method for preparing a Prussian blue analog material using microcapsule sustained-release technology, characterized in that: The method specifically comprises the following steps: (1) dissolving a transition metal source and a sodium source in deionized water in order according to a ratio to obtain a solution A; Dissolve sodium ferroxine and alginate in deionized water in order according to the ratio to obtain solution B; (2) preparing a saturated calcium source solution, heating it to 60-90° C., and then dripping the solution B described in step (1) dropwise into the saturated calcium source solution; filtering after the dripping is completed to obtain transparent microcapsules coated with the solution B; (3) adding the transparent microcapsules containing solution B described in step (2) to solution A described in step (1) under stirring, and continuing the stirring reaction for 6-12 hours to obtain a mixed solution 1; (4) adding carbonate to the mixed solution 1 of step (3) and stirring until completely dissolved; then continuing to add acid solution to the reaction system under stirring until the pH value of the obtained mixed solution 2 is less than 7, and filtering with suction to obtain a Prussian blue analog precursor; (5) Drying and crushing the Prussian blue analog precursor described in step (4) to obtain a Prussian blue analog powder.

2. The method according to claim 1, characterized in that: The transition metal source in step (1) is a transition metal ion salt, and the sodium source is specifically a soluble sodium salt.

3. The method according to claim 1, characterized in that: In step (1), when preparing solution A, the mass ratio of the transition metal source, the sodium source and deionized water is 1-5:1-4:2-5.

4. The method according to claim 1, characterized in that: In step (1), when preparing solution B, the mass ratio of sodium ferroxine, alginate and deionized water is 3-6:4-8:

10.

5. The method according to claim 1, characterized in that: The calcium source in the saturated calcium source solution in step (2) is specifically a soluble calcium salt.

6. The method according to claim 1, characterized in that: The stirring speed in step (3) is 50-150 r / min.

7. The method according to claim 1, characterized in that: The carbonate in step (4) is specifically a soluble carbonate; the acid solution is at least one of citric acid, acetic acid, and hydrochloric acid.

8. The Prussian blue analog material prepared by the method according to any one of claims 1 to 7.

9. Use of the Prussian blue analogue material prepared by the method according to any one of claims 1 to 7 as a positive electrode active material in a sodium ion battery.

10. A sodium ion battery comprising a positive electrode, a negative electrode, a separator and an electrolyte, characterized in that: The active material used in the positive electrode is a Prussian blue analog material prepared by the method according to any one of claims 1 to 7.